Pre- and post-employment issues of bipolar patients and predisposing factors and vocational rehabilitation implications: a new perspective - Rostami, Zeinab; Abedi, Mohammad Reza; Nilforooshan, Parisa (Researcher Bulletin of Medical Sciences, 2022)
Objective: The aim of this study was to explore the employment issues of bipolar patients and their predisposing factors. Materials and Methods: This study was performed using the moose systematic qualitative method, by using research articles that addressed the employment issues of bipolar patients. Initially, 2204 articles were extracted but after primary and secondary screening and studying the full text finally, 15 articles were selected according to predetermined criteria. Results: The extracted employment issues of bipolar patients were divided into two general types of pre- and post-employment issues and the factors causing the employment issues. Pre- and post- employment issues of bipolar patients were divided into three sub-domains (Unemployment, lack of productivity in the workplace, and ethical-communication problems). factors causing bipolar employment issues were divided into three domains (factors related to symptoms of the disorder, psychosocial factors and inappropriate therapeutic interventions). Discussion: Although pre- and post- employment issues of bipolar patients appear to be a major issue both in society and in researches; the underlying causes of these patients' employment issues are also important driving factors, which need attention and consideration and rehabilitation.